Análisis de la red de la empresa intergtel en la ciudad de Babahoyo parroquia Febres cordero - García García, Miguel Eladio (2023)
The analysis of vulnerabilities in the Intergtel network using the MAGERIT methodology revealed worrying weaknesses. Using Nessus, vulnerabilities such as insecure ports (53/tcp, 999/tcp and 2000/tcp) and responses to ICMP echo packets are discovered, signaling possible unauthorized access. These vulnerabilities could expose the network to external attacks, compromising the confidentiality and availability of data. For example, open port 53/tcp could allow unauthorized access. It is crucial to address these weaknesses with measures such as applying security patches and properly configuring firewalls to avoid data loss and interruption of operations.